MENCEGAH DAN MENDIDIK MASYARAKAT TERHADAP PENYAKIT HIPERTENSI, DIABETES DAN ASAM URAT - Juniarti Juniarti; Nazwirman Nazwirman; Lilian Batubara (Universitas Muhammadiyah Ponorogo, 2019)
Hypertension is a disease characterized by an increase in blood pressure that exceeds normal. Diabetes is a disease caused by metabolic disorders that occur in the organs of the pancreas with an increase in blood sugar and are at risk of other diseases. Uric acid is the result of the final metabolism of purines found in the cell nucleus and results in disturbances in the human body. A healthy lifestyle and healthy diet are the right choices to keep yourself free of hypertension, diabetes and gout. It is important to know and prevent disease early, so that education needs to be made about the symptoms, prevention, causes and treatment of the disease. The implementation of community service activities is the empowerment of the Mosque Prosperity Council and worshipers in Banjar Wijaya Tangerang housing by physical examination and counseling to be able to find early risk factors for hypertension, diabetes and gout. The result is the availability of hypertension, diabetes and gout data. People know the symptoms and signs of disease and know how to prevent disease.